Eukaryotic translation initiation factor 5A2 (eIF5A2) regulates chemoresistance in colorectal cancer through epithelial mesenchymal transition. Issue 1 (December 2015) - Bao, Ying; Lu, Yongliang; Wang, Xiang; Feng, Wenming; Sun, Xinrong; Guo, Huihui; Tang, Chengwu; Zhang, Xiaojing; Shi, Qilin; Yu, Hongbin
Abstract Background Chemoresistance is a major obstacle to successful chemotherapy for colorectal cancer. Eukaryotic translation initiation factor 5A2 (eIF5A2), one of the two isoforms in the eIF5A family, has been reported to be a new oncogene in many types of human cancer. In the present study, we aimed to investigate whether eIF5A2 was involved in the chemoresistance to doxorubicin in colorectal cancer. Methods Cell viability was measured by CCK-8 assay with or without doxorubicin treatment. Protein expression was detected by western blot. Tumor cells were transfected with eIF5A2 siRNA or plasmid encoding eIF5A2 to down- or up regulate the expression of eIF5A2. Results We found that eIF5A2-negtive colon cancer cells (HCT116 and HT29) were more sensitive to doxorubicin compare with the eIF5A2-positive cells (LOVO and SW480). Downregulation of eIF5A2 in LOVO and SW480 cells enhanced the chemosensitivity to doxorubicin. On the contrary, overexpression of eIF5A2 reduced doxorubicin sensitivity in colon cancer cells. In addition, eIF5A2 knockdown increased the protein level of E-cadherin and reduced vimentin expression in LOVO and SW480 cells. Meanwhile, upregulation of eIF5A2 potentiated epithelial mesenchymal transition (EMT) in colon cancer cells. Moreover, blockade of EMT with Twist siRNA abolished eIF5A2-regulated chemoresistance in colon cancer cells. Conclusion Our present study demonstrated that eIF5A2 promoted the chemoresistance to doxorubicin via regulation of EMT in colon cancer cells. Therefore, eIF5A2 inhibition may be a new potential strategy for the reversal of drug resistance in colorectal cancer therapy.